2019
DOI: 10.1089/vbz.2018.2401
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus Seroprevalence Among Blood Donors in Hungary

Abstract: Background and Objectives: West Nile virus (WNV) is one of the most important viral zoonotic infections in Hungary; however, no transfusion-transmitted WNV infections have been confirmed so far. In 2016, the number of clinical cases of WNV reported was 44, but the seasonal WNV screening of whole-blood donors has not yet been implemented. Our aims were to assess the WNV RNA reactivity and the prevalence of WNV-specific antibodies in the samples of blood donors collected in 2016. Materials and Methods: WNV RNA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
4
4
2
Order By: Relevance
“…Similar WNV prevalence studies performed in other European countries and in the Mediterranean Basin detected neutralizing antibodies in 1.5% and 2.34% of the population in Greece [26] and in Hungary [27], respectively, while the results of this study are more in line with the prevalence observed in Bulgaria [28].…”
Section: Discussionsupporting
confidence: 91%
“…Similar WNV prevalence studies performed in other European countries and in the Mediterranean Basin detected neutralizing antibodies in 1.5% and 2.34% of the population in Greece [26] and in Hungary [27], respectively, while the results of this study are more in line with the prevalence observed in Bulgaria [28].…”
Section: Discussionsupporting
confidence: 91%
“…Concerning the prevalence of WNV IgG antibody, the results of the present study are in line with many studies conducted in other countries, especially in the Middle East and other parts of the world such as Libya, Algeria, Northern Cyprus, Bolivia, Hungary, Greece and Jordan, as well as in studies carried out in Iran, in which the prevalence of the aforementioned antibody ranged from 2.34% to 8.61% [5,[17][18][19][20][21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 90%
“…In each case, we attempted to characterise the virus using peripheral blood leukocytes or brain and spinal cord samples by virus isolation, nested reverse transcriptase polymerase chain reaction (RT-PCR), real-time RT-PCR and sequencing techniques, as described previously (Kutasi et al, 2011). The virus neutralisation (VN) test was run in 9 of 13 WNND cases and on all control CSF samples as described by Nagy et al (2019).…”
Section: Methodsmentioning
confidence: 99%